A Development Model of Innovative Leadership Competencies as Part of Informal Education to Enhance Learning of Selected Leaders in Thailand - Patchara Vanichvasin, Patchara Vanichvasin (Scholar: Human Sciences, 2015)
This study focused on the competency development model of innovative leadership competencies as part of informal education to enhance learning of selected leaders so that they are prepared to meet the new demands and challenges in the 21st century, especially, the increasing importance of innovation as competitive advantage in today‘s rapidly changing business. It explored and reviewed leadership competencies specific to innovation from theories and practices in both global and Thailand settings to identify the most desirable and common leadership competencies, named as innovative leadership competencies, and to develop the competency model to build those competencies in selected leaders. With purposive sampling technique, the sample comprised of 10 organizational leaders including 30 of other raters as respondents who may rate more than 1 leader. 360 degree questionnaire used were based on widely known instruments and the researcher‘s own experiences in leadership development projects related to leadership competencies. It was used to identify demographic information and to assess expected and actual performance in innovative leadership competencies. Interview with experts was used to validate the effectiveness of recommended leadership development approaches in developing innovative leadership competencies. The study also proposed the innovative leadership competencies development model based on the research findings and recommended application and future research based on research objectives and research results.